Assessment of daily dynamics of postural control in badminton players - Nazarenko, A.S.; Mavliev, F.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to evaluate the daily dynamics of postural control in badminton athletes. Methods and structure of the study. 16 badminton athletes aged 18 to 22 years old, with a level of sportsmanship ranging from candidate for Master of Sports to Master of Sports of the Russian Federation, were examined. Postural stability was assessed in athletes using a biofeedback stability platform in the morning (07:00-08:00), afternoon (12:00-13:00) and evening (18:00-19:00) on a day of complete rest. Results and conclusions. Postural control in athletes demonstrates high individual stability throughout the day. The key factor that significantly affects the quality of the balance function is the presence of visual afferentation. The daily dynamics is most pronounced for the lateral displacement of the pressure center: the morning trend of a shift to the right is replaced by a shift to the left in the afternoon and evens out by the evening. Proprioceptive-vestibular mechanisms work in concert during the day (especially in the absence of vision), while the role of visual control increases during the daytime and evening.